Metabolic‐Immune Suppression Mediated by the SIRT1‐CX3CL1 Axis Induces Functional Enhancement of Regulatory T Cells in Colorectal Carcinoma - Ruiyang Zi; Xiang Zhao; Limei Liu; Yijie Wang; Rui Zhang; Zhiheng Bian; Haoran Jiang; Taorui Liu; Yixin Sun; Han Peng; Xuesong Wang; Fanghao Lu; et al. (Advanced Science)
Abstract Metabolic reprogramming of tumor cells dynamically reshapes the distribution of nutrients and signals in the tumor microenvironment (TME), affecting intercellular interactions and resulting in metabolic immune suppression. Increased glucose uptake and metabolism are characteristic of many tumors. Meanwhile, the progression of colorectal carcinoma (CRC) relies on lipid metabolism. Therefore, investigating the role of glucolipid metabolic reprogramming on tumor immunity contributes to identifying new targets for immune suppression intervention in CRC. Our previous work demonstrated that SIRT1 is the hub gene involved in glucolipid metabolic conversion in CRC. Here, it is found that upregulated SIRT1 in CRC cells increases Treg functionality by promoting the secretion of CX3CL1. The CX3CL1‐CX3CR1 signaling activated transcription factors SATB1 and BTG2, promoting the differentiation of TCF7+ Treg cells into functionally enhanced TNFRSF9+ Treg cells. Multiplex immunofluorescence (mIHC) analysis of a CRC tissue microarray confirmed the promoting effect of CX3CL1 on Treg infiltration. Additionally, the therapeutic efficacy of CX3CR1 inhibitor monotherapy and combination therapy is validated with the PD‐1 antibody in the humanized subcutaneous CRC mouse model. This study elucidates a potential mechanism that metabolic reprogramming of cancer cells collaborates with subsequent immunosuppression to promote CRC progression.